Ball Nut Preload Diagnosis of the Hollow Ball Screw through Support Vector Machine - Huang, Yi-Cheng; Zheng, Jing-Hong (Advances in Technology Innovation, 2018)
This paper studies the diagnostic results of hollow ball screws with different ball nut preload through the support vector machine (SVM) process. The method is testified by considering the use of ball screw pretension and different ball nut preload. SVM was used to discriminate the hollow ball screw preload status through the vibration signals and servo motor current signals. Maximum dynamic preloads of 2%, 4%, and 6% ball screws were predesigned, manufactured, and conducted experimentally. Signal patterns with different preload features are separatedby SVM. The irregularity development of the ball screw driving motion current and rolling balls vibration of the ball screw can be discriminated via SVM based on complexity perception. The experimental results successfully show that the prognostic status of ball nut preload can be envisaged by the proposed methodology. The smart reasoning for the health of the ball screw is available based on classification of SVM. This diagnostic method satisfies the purposes of prognostic effectiveness on knowing the ball nut preload status